Eksistensi Radio 91,6 UMSU FM Sebagai Media Dakwah - Muhammad Rizky Ananda; Muhammad Farhan; Dayana Agustina; Iqbal Syahputra; Luthfi Dzil Ikram (Jurnal Ilmiah Wahana Pendidikan, 2023)
One form of da'wah through mass media is da'wah via radio, as is the case with commercial radio 91.6 UMSU fm. Radio 91.6 UMSU Fm is a business entity owned by Muhammadiyah University North Sumatra (UMSU). 91.6 UMSU FM is commercial radio and not community radio. This makes radio 91.6 Umsu Fm the only campus radio in North Sumatra that is commercial. The type of research used in this research is descriptive analysis which functions to describe or give an overview of the object to be studied through the collected data as it is. In this study the authors describe or describe Radio 91.6 UMSU FM using radio as a medium of propaganda. The author uses data sources related to the existence of Radio 91.6 Umsu Fm as a propaganda medium. Meanwhile, the secondary data used in this study are related radio parties, e-books, journals and the internet. The results showed that since 91.6 UMSU FM radio switched from community radio to commercial radio, UMSU radio experienced very significant progress. Radio 91.6 FM has a YouTube account UMSU FM Medan and also has an application, namely UMSU FM which can be downloaded in the play store and app store. So, people can still listen to 91.6 UMSU FM exist from anywhere and anytime.